A narrative study of Malaysian women with breast cancer sharing their experiences - Wan Mamat, Wan Hasliza; Jarrett, Nikki; Lund, Susi (2021)
Diagnostic pathway is important period for early detection of breast cancer to improve its prognosis. In developed country such as England had introduced faster diagnosis standard to ensure that patients should receive a definitive diagnosis or ruling out of cancer within 28 days of referral. However, there is lack of evidence regarding the patients with breast cancer’s experiences during the diagnostic interval in Malaysia. This study aims to explore what happened to the women during the diagnostic phase before they were diagnosed with breast cancer. 14 participants were recruited from two government hospitals using purposeful sampling. The participants took part in in-depth, face-to-face, one-time, and audio-recorded interviews. All the interviews were subsequently transcribed verbatim and analysed using narrative analysis. Four themes were identified regarding the diagnostic phase: 1) Women who has suspected having breast cancer; 2) Women who experienced false reassurance; 3) Woman who experienced delayed referral; and 4) Women who experienced unconfirmed investigation results. The findings in this study suggest that alert symptoms may prompt immediate action from doctors. However, unexpected delayed may happened due to healthcare workers and system itself. Therefore, healthcare workers should actively refer patients with alert symptoms and actively follow-up patients with non-alert symptoms in the community. Continuing education for healthcare workers might be necessary to improve diagnostic and referral procedures.